Religiosity as an Ethical Infrastructure for Preventing Fraud in Digital Business: Integrating Interfaith, Legal, and Forensic Accounting Perspectives - Robertus Suraji; Lintang Putri Estiarto; Istianingsih Sastrodiharjo (Green Publisher, 2025)
Digital business expands access and efficiency while simultaneously creating new opportunities for fraud through platform opacity, automated decisions, data asymmetry, and cross-border transactions. Existing studies commonly examine religiosity, legal compliance, digital governance, and forensic accounting separately, leaving their complementary relationship underdeveloped. This article aims to formulate an inclusive ethical governance model that positions religiosity as an internal moral infrastructure and combines it with law, organizational controls, and digital forensic accounting. An integrative literature review and normative juridical analysis were applied to recent scholarly works, professional standards, and Indonesian regulations, supported by foundational behavioral theories. The synthesis shows that intrinsic and inclusive religiosity can strengthen moral awareness and inhibit fraud rationalization, but symbolic religiosity cannot substitute for enforceable controls. Effective prevention requires the simultaneous operation of value internalization, accountable digital governance, privacy-respecting analytics, protected reporting channels, and evidence-preserving investigation procedures. The article proposes the Religious Integrity–Forensic Accounting in Digital Ecosystems model, which links moral prevention, structural constraint, technological detection, and corrective response. Its novelty lies in treating religiosity neither as a ceremonial variable nor a stand-alone control, but as one component of a pluralistic, rights-based, and auditable anti-fraud architecture.